Columnar Lithium Metal Anodes - Zhang, Xue‐Qiang; Chen, Xiang; Xu, Rui; Cheng, Xin‐Bing; Peng, Hong‐Jie; Zhang, Rui; Huang, Jia‐Qi; Zhang, Qiang (Angewandte Chemie International Edition, 2017)
The rechargeable lithium metal anode is of utmost importance for high‐energy‐density batteries. Regulating the deposition/dissolution characteristics of Li metal is critical in both fundamental researches and practical applications. In contrast to gray Li deposits featured with dendritic and mossy morphologies, columnar and uniform Li is herein plated on lithium‐fluoride (LiF)‐protected copper (Cu) current collectors. The electrochemical properties strongly depended on the microscale morphologies of deposited Li, which were further embodied as macroscale colors. The as‐obtained ultrathin and columnar Li anodes contributed to stable cycling in working batteries with a dendrite‐free feature. This work deepens the fundamental understanding of the role of LiF in the nucleation/growth of Li and provides emerging approaches to stabilize rechargeable Li metal anodes. Columnar Li deposition is obtained on uniform and dense nucleation sites formed by regulation of LiF. The obvious relation between microstructure and macroscale color provides an emerging descriptor to judge the uniformity of the deposited Li. Ultrathin and stable Li anodes are further developed to meet the intensive demand for high‐energy‐density batteries.